Bentuk dan Strategi Pembinaan Warga Jemaat Dewasa - Sitanggang, Magdha Riadha; Kristina, Dina (ICHTUS: Jurnal Teologi dan Pendidikan Kristiani, 2022)
Abstract: The church has its duty and calling in carrying out the development of congregationmembers; in this case, it is more focused on adult members. The goal is for all adult congregationmembers to take part in building the body of Christ. Through coaching, it is hoped that the maturecongregation will know and grow in the knowledge of Christ. In coaching, there are often obstacles,but that is not an excuse for the church or church advisors not to carry out coaching. Therefore, thepurpose of this writing is to provide an understanding that a mentor is a person who truly believes(has been born again) so that, as a mentor, he has the burden to carry out his calling in fulfilling theGreat Commission. Using a descriptive qualitative method, it can be concluded that, for this reason,church coaches are expected to know the forms and strategies for carrying out coaching. The goal isto make coaching more creative and effective to achieve the coaching goals. In addition, if the coachcan use the coaching strategy properly and is carried out responsibly, many adult congregationmembers will certainly be interested in participating in each coaching program.Keywords: form and strategy, development, adult congregationAbstrak: Gereja memiliki tugas dan panggilannya dalam melaksanakan pembinaan warga jemaat,dalam hal ini lebih difokuskan pada warga jemaat usia dewasa. Tujuannya adalah agar semua wargajemaat dewasa mengambil bagian dalam pembangunan tubuh Kristus. Melalui pembinaandiharapkan jemaat dewasa lebih mengenal dan bertumbuh dalam pengenalan akan Kristus. Dalampembinaan sering ditemui kendala-kendala, tetapi itu bukanlah menjadi alasan untuk gereja ataupembina gereja tidak melaksanakan pembinaan. Oelh karena itu tujuan dari penulisan ini dapatmemberikan pemahan bahwa seorang pembina adalah orang yang sungguh-sungguh beriman(sudah lahir baru), sehingga sebagai pembina ia memiliki beban untuk melakukan panggilannyadalam menggenapkan Amanat Agung. Mengunakan metode kualitatif deskritif dapat disimpulkanbahwa, untuk itu pembina gereja diharapkan mengetahui bentuk dan strategi dalam melaksanakanpembinaan. Tujuannya, agar pembinaan lebih kreatif dan efektif, sehingga tujuan dari pembinaandapat tercapai. Selain itu jika pembina dapat menggunakan strategi pembinaan dengan baik dandilakukan secara bertanggung jawab maka dipastikan banyak warga jemaat dewasa yang tertarikuntuk mengikuti setiap program pembinaan.Kata kunci: bentuk dan strategi, pembinaan, jemaat dewasa